Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil Trimester II di Puskesmas Kota Rih Pekan Kabupaten Serdang Bedagai Tahun 2022 - Zein Agustina Bakara; Eka Purnama; Ernamari Ernamari; Henny Rista (STIKes Ibnu Sina Ajibarang, 2024)
Pregnancy is a continuous chain and starts from ovulation, release of ovum, migration of spermatozoa and ovum, conception process, nidation (implantation) of the endometrium, formation of the placenta and growth and development of the products of conception for approximately 280 days (40 weeks) and no more of 300 days (43 weeks). The length of pregnancy from ovulation to parturition is approximately 280 days (40 weeks). Lower back pain during pregnancy reaches its peak at week 24 until the time of delivery. Back pain is often made worse by backache or what is often called long-standing back pain. This backache was 45% of women when their pregnancy was recorded, they increased 69% at week 28 and almost remained at that level.Type of research conducted This research uses an experimental research plan. Experimental research is a research design used to look for causal relationships with the involvement of research in manipulating independent variables. This research uses a pre-experimental type of pre-post test design in one group (one group pre-post test design).The results of the tabulation research showed that the majority of respondents experienced lower back pain with a scale of 4 very painful, amounting to 17 respondents (53.1%). Lower back pain in pregnant women in the second and third trimesters before carrying out pregnancy exercise where 17 respondents experienced lower back pain on a scale of 4 (very painful) (53.1%), respondents with a scale of 3 (more painful) were 11 people (34 .4%) and respondents with a scale of 2 (slightly more painful) were 4 people (12.5%). Conclusion: Lower back pain in pregnant women in the second and third trimesters before carrying out pregnancy exercise, where respondents experienced lower back pain on a scale of 4 (very painful). There was an effect of reducing back pain before carrying out pregnancy exercise and after carrying out pregnancy exercise on reducing lower back pain in pregnant women. II and III trimesters.